The Utility of Intraoperative Near Infrared Fluorescence (NIR) Imaging with Indocyanine Green (ICG) for the Assessment of Kidney Allograft Perfusion - Edwin Jonathan Aslim; Fang Jann Lee; Valerie Huei Li Gan (Journal of Transplantation)
Background. Near infrared light (NIR) fluorescence imaging with indocyanine green (ICG) has been used in various aspects of surgery, such as in the assessment of vascular anastomosis, tissue perfusion, and the identification of lymph nodes. In this study we evaluated the utility of NIR/ICG fluorescence imaging in kidney transplantation. Materials and Methods. NIR/ICG imaging was used to assess allograft perfusion in n=1 living donor (LDRT) and n=2 deceased donor (DDRT) renal transplantations, performed in February 2017. The allograft arterial and venous anastomoses were done end-to-side to the corresponding recipient external iliacs, and ureteroneocystostomies were performed for urinary reconstructions. After completion of vascular anastomosis, ICG was given as intravenous bolus at 0.3mg/kg, followed by visual assessment of tissue perfusion and vascular anastomoses at 1-minute interval using fluorescence imaging (KARL STORZ NIR/ICG System). Results. Homogenous global fluorescence of the allograft and vascular anastomosis was observed in all 3 cases. Immediate postoperative perfusion studies showed patent inflow and outflow vessels and well perfused transplanted kidneys. Immediate graft function was observed in 2 recipients (1 LDRT and 1 DDRT). One session of haemodialysis was performed in 1 DDRT recipient, for high serum potassium in the immediate postoperative setting, who otherwise had good urine output and serially declining serum creatinine. Conclusions. NIR/ICG fluorescence imaging can be useful in renal transplantation for the intraoperative assessment of allograft perfusion, especially in complex cases with multiple renal arteries and vascular reconstructions.